The owls have come to take us away - Smith, Ronald L. (Ronald Lenard), 1959- (Clarion Books, Houghton Mifflin Harcourt, 2019)
After something strange happens during a camping trip, twelve-year-old alien-obsessed Simon suspects he has been abducted, but was it real or just his overactive imagination?